Transformation in European Defence Supply Chains as Ukraine Conflict Fuels Demand - Roland Hellberg; Martin Lundmark (Scandinavian Journal of Military Studies)
Russia’s full-scale invasion of Ukraine in February 2022 triggered a surge in demand for defence materiel, prompting significant adaptations in manufacturing logistics to meet the needs of the Ukrainian armed forces; donor nations, meanwhile, were prompted to bolster their own military capabilities. This heightened demand for defence materiel has reached levels sufficiently unprecedented as to exceed available supply capacities. This study investigates the factors influencing the evolving dynamics of interactions among states, companies, and supranational agencies within European ammunition and grenade manufacturing supply chains. Grounded in theoretical frameworks on supply chain and of state-defence industry, it explores changes in the defence industry structure, the institutional context, the perspectives of the companies and inter-institutional and corporate relationships. Empirical data were drawn from a range of sources, including official EU and state documents, published analyses, as well as interviews and focus group discussions with Swedish defence industry representatives. Our findings indicate a shift from transactional contracts to trust-based agreements aimed at fostering supply chain resilience and enhancing dynamic capabilities. This study contributes to a deeper understanding and theoretical advancement in managing military and security challenges, with particular emphasis on enhancing readiness, resilience, and the scaling of military capabilities across cross-border defence supply chains.